The added value of internal audit and its role in achieving independence and responsibility: applied research in the Rafidain State Company for Dams implementation (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The added value of internal audit greatly contributes to adding value to the institution, but most departments of economic units in Iraq neglected the role of internal audit and the added value that can be achieved by those institutions, since the term added value of internal audit is a relatively vague term from the premise that what cannot be measured is difficult Determine it, and perhaps descriptive standards for it is the extent of compliance with international auditing standards (IIA).The research aims to study the procedures and results of auditing to verify that they have given an added value to the audit with a positive impact, develop its aspects and research, identify deficiencies for the audit if the results have a negative impact and recommend that they be addressed and the reasons for not achieving the added value, and then this contributes to building a sound scientific and practical methodology in a manner consistent with the performance quality standards and its implications for achieving part of the governance pillars represented in independence and responsibility, and thus achieving administrative reform in state agencies and institutions through the research sample (Al-Rafidain General Company for the implementation of dams).